Nurturing of children through drama and theatre: the case of Intwasa KoBulawayo performances - Matiza, Vimbai M. (Unisa Press, 2016)
Dramatic and theatrical performances have a long history of being used as tools to enhance development in children and youth. In the pre-colonial times there were some forms of drama and theatre used by different communities in the socialisation of children. It is in the same vein that this paper through the Intwasa koBulawayo performances seeks to evaluate how drama and theatre are used to nurture children and youth into different developmental facets of their lives. The only difference which this paper will take into cognisance is that the performances are done in a different environment which is not the one used in the precolonial times. Although these performances were like this, the most important factor is the idea that still children and youth are socialised through these performances. It is also against this backdrop that children and youth are growing up in a globalised environment hence the performances should accommodate people from all walks of life and teach them relevant issues pertaining to life as they live it now. Thus the main task of the paper is to spell out the role of drama and theatre in the nurturing of children and youth through socio-economic and political development in Intwasa koBulawayo festivals.